Self-evaluation in Distance Education of Biology Program FKIP-Universitas Terbuka - Leonard Raden Hutasoit; Anna Ratnaningsih; Krisna Iryani; Tri Wahyuningsih (Postgraduate, University of Mataram, 2023)
The purpose of this research is expected to help the S1 Biology Education Study Program FKIP-UT in improving academic and administrative services for users. In detail, the objectives of this study are: (1) The effectiveness of the services that have been provided by the Biology Education S1 Study Program FKIP-UT to service users; (2) Student services of the S1 Biology Education Study Program FKIP-UT; (3) Service user satisfaction of the S1 Biology Education Study Program FKIP-UT; (4) Characteristics of the learning process of the S1 Biology Education Study Program FKIP –UT; (5) Learning experience of service users of the S1 Biology Education Study Program FKIP-UT. The research used quantitative and qualitative methods. Quantitative methods are carried out by surveying all graduates/ students using questionnaires [letters, forms]. While the qualitative method was carried out for limited respondents who were randomly selected proportionally through [online] interviews. The results of this study include data analysis of the effectiveness of services that have been provided by the Biology Education S1 Study Program FKIP-UT to service users, as many as 62.4% are satisfied with the Subject Material Books used, 48.5% are online tutorials, 41.3% Webinars and 56.2% are final exams. As many as 62% of respondents already know the student services of the S1 Biology Education Study Program FKIP-UT regarding reasoning, interests and talents, 60% regarding career guidance and 45.8% regarding welfare and easy access. Satisfaction with the learning experience in the S1 Biology Education Study Program, respondents were satisfied and very satisfied in discussions, tutorial assignments, practices and practicums. With respondents who are dissatisfied with academic and administrative services, it is necessary to improve services and socialization for those who have difficulty accessing services.